- #36
Swapnil
- 459
- 6
mtanti said:Hey man, I know how to prove by induction, I just don't know what I'm doing. Is it deductive or not?
RTP S(2n-1) = n^2
STEP 1: Prove that statement is true for n=1
2(1)-1 = 1^2
1 = 1
QED
STEP 2: Prove that if statement is true for n, it is also true for n+1
RTP S(2n+1) = (n+1)^2 [Is this what this step is all about?]
S(2n+1) = n^2 + n+1
RHS cannot be transformed into (n+1)^2, therefore S(n+1) will not work, therefore S(n) is not true.
QEDLESS
I think you are still a bit confused. I think it would help if you would stop using S(something) to mean two different things. You sometimes let S stand for summation and sometimes you let it stand for statement.
Here is the way you do the proof:
You first let your S(n) (the statement) stand for the given relationship (here instead of saying "S(n) = something" I will say "S(n) [=] something" since S(n) is a statement and not your typical algebraic relationship) i.e
[tex] S(n)\,[=]\,\sum_{i=1}^{n} 2i-1 = n^2[/tex]
[tex] \Rightarrow 1 + 3 +...+ 2n-1 = n^2[/tex]
Now we know that S(n+1) is the following (simply substitute "n+1" wherever you see "n")
[tex] S(n+1)\,[=]\,\sum_{i=1}^{n+1} 2i-1 = (n+1)^2[/tex]
[tex] \Rightarrow 1 + 3 +...+ 2n-1 + 2(n+1)-1 = (n+1)^2[/tex]
[tex] \Rightarrow 1 + 3 +...+ 2n-1 + 2n+1 = (n+1)^2[/tex]
So to "expand" S(n) into S(n+1) the first thing we can do is add 2n+1 to both sides of S(n) i.e.
[tex] S(n)\,[=]\,1 + 3 +...+ 2n-1 + 2n+1 = n^2 + 2n + 1[/tex]
Notice that [tex](n+1)^2 = n^2 + 2n + 1[/tex] which is exactly what we have on the RHS. Thus we have in a way "derived" S(n+1) just from S(n). Thus, S(n) => S(n+1). Noiw since the base case obviously works, we have completed our inductive proof.
Last edited: